Competitive advantages through generative AI: Expertise as the key to implementation - Immo Brüggemann; Stephan Buse; Janin Partuschke; Nohemi Villarreal (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2025)
In order to understand generative AI and its mechanisms of action, players need a high level of abstraction (Saitta and Zucker, 2013). However, many companies lack the necessary expertise for the technology. In addition to cultural factors, this lack of expertise is the main barrier to a results-oriented implementation of the technology (Campos Zabala, 2023). To identify valuable fields of application, companies need to understand the expertise in the decision-making processes of their own activities. The article shows concrete examples and steps that companies can use to test and apply new technological possibilities to their own use cases.
Keywords: 650